Dietary prebiotics and probiotics influence the growth performance, feed utilisation, and body indices of snakehead (Channa striata) fingerlings - Munir M.B.; Hashim R.; Abdul Manaf M.S.; Mohd Nor S.A. (Penerbit Universiti Sains Malaysia, 2024)
Indexed by Scopus